Phenotypic and Functional Characterizations of Mesenchymal Stem/Stromal Cells Isolated From Human Cranial Bone Marrow - Yang, Kaichuang; Lu, Ruijie; Lu, Jianan; Fan, Shucai; Zhang, Qiang; Lou, Zijian; Ma, Yuyuan; Lu, Gang; Pan, Ruolang; Zhang, Jianmin (Frontiers in Neuroscience, 2022)
Mesenchymal stem/stromal cells (MSCs) are adult stem cells that were originally isolated from bone marrow. In contrast to long bone-derived MSCs that have been extensively characterized, our knowledge regarding to MSCs isolated from flat bones (e.g., cranial bones) remain less clear. In this study, MSCs were purified from human cranial bone marrow (CB-MSCs) and their transdifferentiation capacity and immunomodulatory functions were further characterized. Phenotypic analysis of CB-MSCs demonstrated high expression of CD73, CD90 and CD105 while negative for CD14, CD34 and HLA-DR. Further in vitro differentiation assay shown that CB-MSCs capable of differentiating into cell types of mesenchymal origin (i.e., adipocytes, osetoblasts and chondrocytes) and collectively, these results indicated that cells isolated from cranial bone marrow in this study are bona fide MSCs according to the minimal criteria proposed by the International Society for Cellular Therapy. Following in vitro expansion, single colony-derived CB-MSCs (scCB-MSCs) were obtained and confocal microscopy analysis further revealed functional heterogeneity within primary CB-MSCs. Specifically, obtained scCB-MSCs exhibited different propensity to differentiate into distinct types of neural-like cells as scCB-MSCs robustly expressed Olig2 and GABA, respectively. Furthermore, immunomodulatory roles of scCB-MSCs were evaluated following co-culture with human peripheral blood lymphocytes and results shown that co-culturing with scCB-MSCs significantly suppressed lymphocyte proliferation and promoted differentiation of lymphocytes into regulatory T cells but not Th1/Th17 phenotype. Overall, our results indicated that CB-MSCs exhibited clonal heterogeneity with marked propensity to differentiate into neural-like cells and this might represent promising candidates for the treatment of neurodegenerative diseases.